Live virtual machine migration based on improved pre-copy approach - Fei Ma; Feng Liu; Zhen Liu (2010 IEEE International Conference on Software Engineering and Service Sciences, 2010)
Live migration of virtual machine has attracted significant attention in recent years. It facilitates system online maintenance, load balancing, fault tolerance and power management. Although pre-copy approach can balance the downtime and total migration time of contradictions, it will cap the number of copying iterations to the maximum number of iterations since the writable working set is not guaranteed to converge across successive iterations, especially when the VM is executing a largely read-intensive workload. In this paper, we improve the pre-copy approach on Xen 3.3.0. We add a bitmap page in our improved pre-copy approach, which marks those frequently updated pages. By the judge in the iteration process, we put those frequently updated pages into the page bitmap, and those pages can only be transmitted in the last round of the iteration process. This can ensure that those frequently updated pages are transmitted just once in the iteration process. Experiment demonstrates that compared with pre-copy, our improved pre-copy approach can reduce 34% of total transferred data and 32.5% of total migration time total transferred data on average. More importantly, our approach can complete the iteration process no more than 5 times.